1977
DOI: 10.1002/jcu.1870050109
|View full text |Cite
|
Sign up to set email alerts
|

The antepartum findings of conjoined twins

Abstract: Various estimates abound as to the incidence of conjoined (Siamese) twins, but they are indeed uncommon. The probability of their occurance has been calculated to be once in every 12,000 to once in every 100,000 deliveries. Although uncommon, the antepartum diagnosis can be extremely important to the twins and the mother, if only to spare the trauma of a trial by labor. The findings, both radiographic and ultrasonic, are presented herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Os gêmeos unidos são classificados, de acordo com o local do corpo onde a união fetal é dominante, em cinco tipos predominantes: toracópagos (tórax, 30-40%), onfalópa-gos (abdome, 25-30%), piópagos (sacro, 10-20%), isquiópagos (pelve 6-20%) e craniópagos (cabeça, 2-16%). O diagnóstico ultra-sonográfico pré-natal desta anomalia foi relatado primeiramente em 1977 14 . Desde este relato, numerosos casos têm sido descritos na literatura [15][16][17] .…”
Section: Discussionunclassified
“…Os gêmeos unidos são classificados, de acordo com o local do corpo onde a união fetal é dominante, em cinco tipos predominantes: toracópagos (tórax, 30-40%), onfalópa-gos (abdome, 25-30%), piópagos (sacro, 10-20%), isquiópagos (pelve 6-20%) e craniópagos (cabeça, 2-16%). O diagnóstico ultra-sonográfico pré-natal desta anomalia foi relatado primeiramente em 1977 14 . Desde este relato, numerosos casos têm sido descritos na literatura [15][16][17] .…”
Section: Discussionunclassified
“…Whenever monozygotic twinning is observed, conjoining should be suspected. Wilson et al 8 suggested that the presence of polyhydramnios and both twins in breech or in face-to-face position should alert the sonographer to the possibility of conjoined twins. Koontz et al 9 suggested that some other sonographic findings are also associated with conjoined twins.…”
Section: Discussionmentioning
confidence: 99%
“…The first reported case of conjoined twins was recorded in A.D. 1 100 (12) and the first recorded case diagnosed prenatally by ultrasound B-scan was in 1977 (18). The malformation is thought to result from an incomplete, delayed fission of the inner cell mass, which occurs after the 14th day of fertilization (16).…”
Section: Discussionmentioning
confidence: 99%